2021
DOI: 10.3390/agriculture11040305
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower Husk Biochar as a Key Agrotechnical Factor Enhancing Sustainable Soybean Production

Abstract: Climate change has a decisive impact on the physical parameters of soil. To counteract this phenomenon, the ongoing search for more effective agri-technical solutions aims at the improvement of the physical properties of soil over a short time. The study aimed to assess the effect of biochar produced from sunflower husks on soil respiration (SR), soil water flux (SWF), and soil temperature (ST), depending on its dose and different soil cover (with and without vegetation). Moreover, the seed yield was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…65 ± 5 m 2 ∙g −1 , which is a value similar to the results obtained by Aselkand et al [ 54 ] and Tomczyk et al [ 55 ] for the biochar from woodchips. This surface area is much larger than that of the biochar used by Klimek-Kopyra et al [ 46 ] for water retention and nitrogen retention in soils (approx. 19 m 2 ∙g −1 ) but significantly lower than that of the biochar applied in the sorption of heavy metals [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…65 ± 5 m 2 ∙g −1 , which is a value similar to the results obtained by Aselkand et al [ 54 ] and Tomczyk et al [ 55 ] for the biochar from woodchips. This surface area is much larger than that of the biochar used by Klimek-Kopyra et al [ 46 ] for water retention and nitrogen retention in soils (approx. 19 m 2 ∙g −1 ) but significantly lower than that of the biochar applied in the sorption of heavy metals [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 86%
“…The biochar used in the research is a material available commercially on the market and was obtained from coniferous woodchips as a result of pyrolysis in the thermalization energy recovery module at 550 °C for 30 min [ 29 , 42 ]. As Lehmann [ 43 ] and Jin et al [ 44 ] have reported, this temperature allows for obtaining biochar with the most favorable properties, i.e., high carbon content, cation exchange capacity, and a specific surface area, which are important in the biological methods of waste treatment and biochar application to soils [ 45 , 46 , 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…The seed yield was determined based on the structure of the soybean yield and the degree of pod pinching as a parameter of plant adaptation to habitat conditions. A detailed description of the experiment, methodology, chemical composition of biochar used in the experiment and data on soil properties can be found in Klimek-Kopyra (2021) [38] and Kubo ń et al [39].…”
Section: Agronomic Methodsmentioning
confidence: 99%
“…Mona et al [3] and Klimek-Kopyra et al [35] note significant differences in the quality of biochar in terms of plant cultivation suitability. These authors stated that microalgae biochar was characterized by a higher sorption capacity, increasing the use of elements applied with fertilizers.…”
Section: Introductionmentioning
confidence: 99%